Associations between Missing Teeth with Unmet Needs and Socioeconomic Status among South Korean Dentate Government Employees - Hae-Young Kim, DDS, PhD; Seung-Wook Lee, PhD; Sung-Il Cho, MD, PhD (Blackwell Synergy, 2007)
This study aims to examine associations between missing teeth with unmet needs (MTUN) and socioeconomic status, represented by income and place of residence.